Two new species of the bamboo-feeding planthopper genus Neobelocera Ding & Yang, 1986 from China (Hemiptera, Fulgoroidea, Delphacidae) - Li, Hong-Xing; Yang, Lin; Chen, Xiang-Sheng (European Journal of Taxonomy, 2020)
Two new species of the bamboo-feeding genus Neobelocera Ding & Yang, 1986, N. biprocessa sp. nov. and N. russa sp. nov., are described and illustrated from southwest China (Hainan and Guizhou), giving the genus nine species in total. A key is provided to separate all species.